PD-L1 Expression on Tumor Cells Is Associated With a Poor Outcome in a Cohort of Caucasian Nasopharyngeal Carcinoma Patients - Minichsdorfer, Christoph; Oberndorfer, Felicitas; Krall, Christoph; Kornek, Gabriela; Müllauer, Leonhard; Wagner, Christina; Fuereder, Thorsten (Frontiers in Oncology, 2019)
Background: Nasopharyngeal carcinoma (NPC) is endemic in East Asia but rare in the western world. Programmed death ligand 1 (PD-L1) expression on NPC correlates with clinical outcomes. However, data for Caucasian NPC patients are missing. Thus, we performed this retrospective analysis for investigating the potential association of immune checkpoint protein expression with outcome parameters in Caucasian NPC patients. Methods: Fifty-five patients with NPC treated between 1993 and 2018 at the Medical University of Vienna were identified. After the exclusion of Asian patients, data on baseline demographic, tumor stage, overall survival (OS), and disease-free survival (DFS) of 30 patients were analyzed. Their tumor samples were stained and scored (low vs. high) for PD-L1, programmed death receptor 1 (PD-1), lymphocyte activating gene 3 (LAG3), and cluster of differentiation 8 (CD8) antibodies. Statistical analysis was performed with Kaplan-Meier plots and log-rank test. Estimated hazard ratios of dichotomized analysis were calculated, together with 95% confidence intervals and p-values of Wald tests. Results: PD-L1 expression was ≥50% in 6 (20%) patients, whereas 19 (63%) had ≥1% expression and 5 (17%) tumor samples were PD-L1-negative. While sex and age had no impact on DFS or OS, <50% PD-L1 expression on tumor cells (TC) was associated with a significantly longer OS (log rank test p = 0.037; HR 0.275; 95% CI 0.073–1.03). There was no influence on DFS (log rank test p = 0.34; HR 0.599; 95% CI 0.208–1.728). However, <10% PD-L1 expression on tumor infiltrating lymphocytes (TILs) was correlated with a worse DFS (log rank test p = 0.0057; HR 4.06; 95% CI 1.389–11.868). LAG3 expression or the number of TILs did not play any prognostic role in our population. Conclusion: The PD-L1 expression rate on Caucasians was comparable to that in Asian patients. Although these results have to be interpreted with caution due to the limited number of Caucasian patients available, our data suggest that ≥50% PD-L1 expression on TC is associated with a poor outcome, while ≥10% PD-L1 expression on TILs is correlated with improved DFS. A prospective biomarker analysis of a predefined Caucasian NPC subpopulation would be desirable in future trials.